Tourism and the Transformation of Social Capital in Rural Communities (2023)
Tourism is a social phenomenon that produces changes in the territorial and relational spheres. Its development depends precisely on the context, structures, processes, local people, tourists, and those who participate in the economic activity in the territory. This leads to the generation of diverse sociocultural relationships, establishing a certain level and type of social capital. The objective of this review article is to identify processes of transformation of social capital due to the influence of tourism in rural communities, based on the review of worldwide cases published in the Scopus, Web of Science and Lens databases; articles published in English and Spanish from 2010 to 2022 were selected, analyzed, and classified. The research makes it possible to describe the elements that have strengthened or eroded social capital.